THE INFLUENCE OF RELIGIOSITY, PRODUCTS AND SERVICES TOWARDS THE INTERESTS OF MUSLIM COMMUNITIES IN GARUT REGENCY TO TRANSACT WITH SHARIA BANKS - Rani Surya Resiana; Cupian Cupian (Universitas Airlangga, 2020)
The purpose of this research is to find out what is the influence of religiosity, product, and service on Islamic community’s interest in Garut to perform financial transaction with sharia banking. The research method used was quantitative descriptive method. The sample of this study are 100 person from community of Garut that actively do the transaction with Sharia Bank Mandiri, Sharia Bank BJB, and Bank Muamalat. The result of the study shows that simultaneously, religiosity, product, and service factors together influences the Islamic community’s interest in Garut to perform financial transactions with sharia banking. However, partially or individually just two variabels, it is religiousity and service that affect significantly while product variabel not is not affect significantly influences the Islamic community’s interest in Garut to perform transaction with sharia banking.Keywords: Sharia Banking, Religiousity, Transaction, Muslim Community